Reproductive Mode and Conflict Shape the Evolution of Male Attributes and Rate of Speciation in the Fish Family Poeciliidae - Reznick, David N.; Travis, Joseph; Pollux, Bart J. A.; Furness, Andrew I. (Frontiers in Ecology and Evolution, 2021)
Sexual conflict is caused by differences between the sexes in how fitness is maximized. These differences are shaped by the discrepancy in the investment in gametes, how mates are chosen and how embryos and young are provided for. Fish in the family Poeciliidae vary from completely provisioning eggs before they are fertilized to providing virtually all resources after fertilization via the functional equivalent of a mammalian placenta. This shift in when females provision their young relative to when an egg is fertilized is predicted to cause a fundamental change in when and how sexual conflict is manifested. If eggs are provisioned before fertilization, there should be strong selection for females to choose with whom they mate. Maternal provisioning after fertilization should promote a shift to post-copulatory mate choice. The evolution of maternal provisioning may in turn have cascading effects on the evolution of diverse features of the biology of these fish because of this shift in when mates are chosen. Here we summarize what these consequences are and show that the evolution of maternal provisioning is indeed associated with and appears to govern the evolution of male traits associated with sexual selection. The evolution of placentas and associated conflict does not cause accelerated speciation, contrary to predictions. Accelerated sSpeciation rate is instead correlated with accelerated by the evolution of male traits associated with sexual selection, which implies a more prominent role of pre-copulatory reproductive isolation in causing speciation in this family.